2022
DOI: 10.1038/s42003-022-03312-0
|View full text |Cite
|
Sign up to set email alerts
|

Failure of DNA double-strand break repair by tau mediates Alzheimer’s disease pathology in vitro

Abstract: DNA double-strand break (DSB) is the most severe form of DNA damage and accumulates with age, in which cytoskeletal proteins are polymerized to repair DSB in dividing cells. Since tau is a microtubule-associated protein, we investigate whether DSB is involved in tau pathologies in Alzheimer’s disease (AD). First, immunohistochemistry reveals the frequent coexistence of DSB and phosphorylated tau in the cortex of AD patients. In vitro studies using primary mouse cortical neurons show that non-p-tau accumulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 66 publications
3
18
1
Order By: Relevance
“…Yujun et al showed impaired neuronal bioenergetics and neuroinflammation in the progression of AD, and nicotinamide riboside treatment reduced pyrin domain containing 3 (NLRP3) inflammasome expression, DNA damage, apoptosis, and cellular senescence in the AD mouse brains 43 . Furthermore, protective effects against nuclear damage have been reported for microtubule associated protein tau (MAPT), another crucial protein in AD known for its accumulation 44 . Alternatively, the potential of senescent cell clearance-senolysis-to ameliorate phenotypes associated with aging and age-related diseases has been documented 45 , and AD could also be improved through senolysis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Yujun et al showed impaired neuronal bioenergetics and neuroinflammation in the progression of AD, and nicotinamide riboside treatment reduced pyrin domain containing 3 (NLRP3) inflammasome expression, DNA damage, apoptosis, and cellular senescence in the AD mouse brains 43 . Furthermore, protective effects against nuclear damage have been reported for microtubule associated protein tau (MAPT), another crucial protein in AD known for its accumulation 44 . Alternatively, the potential of senescent cell clearance-senolysis-to ameliorate phenotypes associated with aging and age-related diseases has been documented 45 , and AD could also be improved through senolysis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Tau plays an important role in the protection against DNA damage [ 134 , 135 ]. Moreover, DSBs’ induction immediately increases Tau in the nuclear fraction of primary mouse cortical neurons [ 136 ]. The phosphorylation of the AT8 site is specific for senile chromatin [ 28 ] and has been directly related to DSBs’ induction in cortical neurons [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DSBs’ induction immediately increases Tau in the nuclear fraction of primary mouse cortical neurons [ 136 ]. The phosphorylation of the AT8 site is specific for senile chromatin [ 28 ] and has been directly related to DSBs’ induction in cortical neurons [ 136 ]. In granular neurons, the double AT100 and AT8 presence seems to determine the nuclear Tau function interacting with aged chromatin, favoring DSBs’ repair [ 136 , 137 ] and maintaining genomic stability [ 43 , 138 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 This is consistent with recent evidence that both tau and synuclein play an important role in the repair of DNA damage. 10,11 Whether the cycad toxins MAM and/or β-N-methylamino-L-alanine (L-BMAA) induce pathogenesis by modifying MGMT epigenetically is unknown, 4 especially because MGMT methylation is affected by environmental factors, as well as genetic variation. 13 A recent report in these pages by Chung et al 14 shows that MGMT variants are associated with inherited forms of AD, particularly among women lacking the apolipoprotein E (APOE) ɛ4 allele.…”
Section: Highlightsmentioning
confidence: 99%